The influence of school location and their children's nutritional model on the risk of obesity in Poland- pilot study - Długoński, Łukasz; Platta, Anna; Skotnicka, Magdalena (Frontiers in Nutrition, 2025)
Problems with overweight and obesity during childhood and adolescence are associated with negative health effects that can impact a lifetime. Eating habits and lifestyles formed early in life influence our health in the future. These habits are difficult to change and often persist into adulthood. The aim of the study was to investigate the influence of residence and school attendance on the occurrence of childhood overweight and obesity. The survey, in the form of a questionnaire, was conducted among mothers or legal guardians of children attending public primary schools in the Pomeranian Voivodeship in Poland. A total of 515 individuals participated in the study. The questionnaire was prepared based on the Food Frequency Questionnaire (FFQ) and the Child Eating Behavior Questionnaire (CEBQ). The study showed that children living in rural areas are more prone to developing obesity and overweight. Among children living in rural areas, 46.89% are overweight, while in cities, 40.85% are overweight. Regarding children suffering from obesity, the percentage of those attending rural schools is 15.79%, while only 1.63% of obese children attend urban schools. Additionally, it was shown that children from rural areas more frequently exhibit poor eating habits and incorrect dietary patterns and behaviors, which mainly include eating lunch at school and simultaneously consuming nutrient-dense at home. Among children from rural areas, 74.07% consume sweets without restrictions, compared to only 25.93% of children from cities. The unrestricted consumption of salty snacks by children attending rural schools is as high as 75.64%, compared to 24.36% for children attending urban schools. The results of the current study indicate that residence and school attendance can determine the risk of developing overweight and obesity. Our findings show that children from rural areas have a high rate of obesity, highlighting the necessity to propose new solutions and tools to support proper nutrition, with particular emphasis on children from rural environments.